Betulinic Acid Exerts Cytoprotective Activity on Zika Virus-Infected Neural Progenitor Cells - Cavalcante, Bruno R. R.; Aragão-França, Luciana S.; Sampaio, Gabriela L. A.; Nonaka, Carolina K. V.; Oliveira, Moisés S.; Campos, Gúbio S.; Sardi, Silvia I.; Dias, Beatriz R. S.; Menezes, Juliana P. B.; Rocha, Vinícius P. C.; Rossi, Erik A.; Paredes, Bruno D.; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Zika virus (ZIKV), a member of the Flaviviridae family, was brought into the spotlight due to its widespread and increased pathogenicity, including Guillain-Barré syndrome and microcephaly. Neural progenitor cells (NPCs), which are multipotent cells capable of differentiating into the major neural phenotypes, are very susceptible to ZIKV infection. Given the complications of ZIKV infection and potential harm to public health, effective treatment options are urgently needed. Betulinic acid (BA), an abundant terpenoid of the lupane group, displays several biological activities, including neuroprotective effects. Here we demonstrate that Sox2+ NPCs, which are highly susceptible to ZIKV when compared to their neuronal counterparts, are protected against ZIKV-induced cell death when treated with BA. Similarly, the population of Sox2+ and Casp3+ NPCs found in ZIKV-infected cerebral organoids was significantly higher in the presence of BA than in untreated controls. Moreover, well-preserved structures were found in BA-treated organoids in contrast to ZIKV-infected controls. Bioinformatics analysis indicated Akt pathway activation by BA treatment. This was confirmed by phosphorylated Akt analysis, both in BA-treated NPCs and brain organoids, as shown by immunoblotting and immunofluorescence analyses, respectively. Taken together, these data suggest a neuroprotective role of BA in ZIKV-infected NPCs.